How TikTok Boosts Electability in Indonesia's 2024 Presidential Race: Bagaimana TikTok Meningkatkan Elektabilitas dalam Pemilihan Presiden Indonesia 2024 - Nikmah, Hadiyatun; Salsabila, Chorida Fara; Wicaksono, Satrio; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the role of TikTok in enhancing the electability of presidential candidates in Indonesia's 2024 election. Using a quantitative approach with observation and documentation, the research analyzes how TikTok influences political image-building. The findings show that TikTok is pivotal in generating public discussion and increasing candidate visibility. Despite a peak in related studies in 2018, there is a notable gap in recent research, highlighting opportunities for further investigation. This study underscores TikTok's significance in political communication and its impact on electoral success. Highlight: TikTok boosts presidential candidates' visibility and electability. TikTok trends influence public political perceptions. Recent research gap on TikTok's electoral impact. Keyword: TikTok, electability, presidential election, political communication, Indonesia